Mental Health Care Utilization in Latinx Young Adults Who Grew Up in Rural or Small-Town U.S. Communities by Racial/Ethnic Immigrant Generational Status - Mata-Diaz, Sandra (My University, 2023)
Purpose: To evaluate (1) differences in mental health care utilization across young adulthood by racial/ethnic immigrant generational status for young adults who grew up in a rural setting, (2) whether these differences are explained by language barriers and health insurance coverage, and (3) whether these differences vary longitudinally over the young adulthood period.Methods: Four years of longitudinal data from 1530 young adults that participated in the Community Youth Development Survey (CYDS) were analyzed. Self-reported mental health care utilization was assessed from age 19 to age 26 along with racial/ethnic immigrant generational status based on the individual’s and their parents’ country of birth. Multilevel modeling was used to evaluate differences in mental health care utilization among Latinx children of immigrants (COI), Latinx children of non-immigrants (CONI), and non-Latinx White CONI. Results: Latinx CONI (OR = 2.51, 95% CI: 1.18, 5.34) and White CONI (OR = 2.50, 95% CI: 1.36, 4.61) both had higher odds of utilizing mental health care compared to Latinx COI. When bilingual status was included in the model, these differences were reduced and the findings were no longer statistically significant (Latinx CONI: [OR=1.56, 95% CI: 0.63, 3.87] and for White CONI [OR=1.30, 95% CI: 0.52, 3.26]). Health insurance coverage did not account for differences in mental health care utilization. There were no differences in these associations over time by racial/ethnic immigrant generational status. Conclusion: Mental health care utilization differs by racial/ethnic immigrant generational status, and this is partially accounted for by language barriers. This points to the importance of culturally competent and bilingual mental health care providers in rural settings to improve immigrant health. It further highlights the heterogeneity present within the Latinx population and the need for further research into understanding how health care utilization varies across the population.
Thesis (Master's)--University of Washington, 2023
Keywords: Generational status; Immigrant Health; Latinx; Longitudinal Study; Mental health care utilization; Rural setting; Epidemiology; Mental health; Epidemiology